Removal of Dyestuffs from Aqueous Solutions Using Maize Cob - Babu Jose R. Wilfred Sugumar, V.; Gopalan, R. (Asian Journal of Chemistry, 2010)
The adsorption of the dyes, malachite green, congo red and methyl red onto maize cob, an agricultural waste, was studied. Isotherm studies were carried out to find out the maximum adsorption capacity of maize cob for the dyestuffs. Adsorption was found to follow Freundlich isotherm model. Contact-time experiments were carried out in an agitated batch adsorber to assess the effect of temperature and maize cob particle size on adsorption.